Pembuatan Bioetanol dari Campuran Kulit Nenas dan Pepaya Secara Fermentasi dengan Variasi Massa Ragi Roti - Salian Salian; Vera Viena; Irhamni Irhamni (Fakultas Teknik, 2022)
Fruit peel waste was one of carbohydrate feedstock for producing bioethanol. The research main purpose was analyzing the impact of yeast mass addition in fermentation process of pineapple and papaya peels mixture (PPPM) for making of bioethanol. The procedure was carried out by adding 10 grams of glucose for each treatment, the yeast Saccharomyces cerevisiae mass varied from 1 to 4 % w/v, and the fermentation time were 24, 48, 72 and 96 hours at temperature 30 0C. The initial sugar containment was tested by Brix refractometer and the bioethanol composition was characterized using Gas Chromatography-Mass Spectrometry. The initial sugar content of the PPPM starter was range from 3 – 5 %. By addition of yeast weight (1 - 4% w/v), the comparison of bioethanol yield were in range 2 to 5% using hydrometer alcohol and in the range of 3,013–3,403% while using GC-MS. In conclusion, the sugar content of PPPM substrate and yeast starter percentage have significant effect on bioethanol earning